Kontribusi Pajak Dan Bea Balik Nama Kendaraan Bermotor Di Provinsi Jawa Timur (Studi Kasus Pada Masa Pandemi Covid-19) - Dina Nur Safitri (SUSTAINABLE JURNAL AKUNTANSI, 2021)
This study aims to determine how is the contribution of PKB (Taxes) and BBNKB (Transfer Fees for Motorized Vehicles) in East Java Province to the Regional Revenue. The study is conducted at the Regional Revenue Agency of East Java Province with a qualitative descriptive method. The data are collected in the form of secondary data, field surveys in the form of documentation. The results of the study show that PKB and BBNKB revenues in 2018 - 2020 in East Java Province is that the average contribution of motor vehicle taxes (PKB) to the regional revenue is 40.10% called as in a good category and the average contribution of motor vehicle title transfer fees (BBNKB) to the regional revenue is 20,10% called as in the medium category. However, the revenue of motor vehicle tax and motor vehicle transfer fees always exceeds the target. The Regional Government policy on the increasing of PKB and BBNKB revenues during the Covid-19 pandemic is to waive fines for late payment of PKB as well as exempt administrative sanctions of PKB and BBNKB and provide basic payment cuts of PKB for two-wheelers and four-wheelers. In order to increase the contribution level of PKB and BBNKB to the regional revenue of East Java Province, cooperation between the government and taxpayers is needed.Keywords: Contribution, Regional Revenue, PKB, BBNKB, the Covid-19 PandemicPenelitian ini bertujuan untuk mengetahui seberapa besar kontribusi PKB dan BBNKB di Provinsi Jawa Timur terhadap Pendapatan Asli Daerah. Penelitian dilakukan di Badan Pendapatan Daerah Provinsi Jawa Timur dengan metode yang bersifat deskripsi kualitatif, yaitu dengan mengumpulkan data yang berupa data sekunder, survey lapangan berupa dokumentasi. Hasil Penelitian menunjukkan bahwa penerimaan PKB dan BBNKB tahun 2018 – 2020 di Provinsi Jawa Timur yaitu rata-rata kontribusi Pajak Kendaraan Bermotor terhadap PAD adalah sebesar 40,10 persen dalam kategori baik dan rata-rata kontribusi Bea Balik Nama Kendaraan Bermotor terhadap PAD adalah sebesar 20,10 persen dalam kategori sedang. Namun, penerimaan Pajak Kendaraan Bermotor dan Bea Balik Nama Kendaraan Bermotor selalu melebihi target yang sudah ditetapkan. Kebijakan Pemerintah Daerah terhadap peningkatan penerimaan PKB dan BBNKB pada masa pandemi Covid-19 yaitu dengan membebaskan denda keterlambatan PKB serta membebaskan sanksi administratif PKB dan BBNKB dan memberikan potongan pokok PKB untuk roda dua dan roda empat. Supaya tingkat kontribusi dari PKB dan BBNKB terhadap PAD Provinsi Jawa Timur terus meningkat maka dibutuhkannya kerjasama antara pemerintah dan wajib pajak. Kata Kunci: Kontribusi, PAD, PKB, BBNKB, Covid-19.